The study on students' perception towards absenteeism in UiTM Kota Bharu / Nur Aida Husna Mohamed Shafie, Nurul Syazana Zulkofli and Mohamad Idham Ariff Roslan - Mohamed Shafie, Nur Aida Husna; Zulkofli, Nurul Syazana; Roslan, Mohamad Idham Ariff (2019)
Absenteeism among student has become a major issue of concern worldwide. Student absenteeism was defined as a period of time when a student is not attending school and is out of school for no good reason. The literature review related to the attendance of student exposed absenteeism as a problem that can affect all education stakeholders directly or indirectly. Absenteeism among students also can lead to negative effect such as student's academic performance and many social problems. Hence, this study was carried out with the intention to discover the perception of UiTM students' about absenteeism. It aims to ascertain the perceptions of UiTM students' on the reasons why students are absent from the class and the effect of absenteeism on their academic performance. Few factors involving student problem, peer influence, teaching style and class environment factor were being investigated in this study. In addition, a correlative design and cross-sectional study were used in this study and the findings of the study revealed the 273 perceptions of UiTM Kota Bharu students. Each of the students' perception data was obtained by distributed self-administered questionnaire to the selected respondents. The proportionate stratified random sampling was used to select the respondent from each course in UiTM Kota Bharu. To gain variety of findings in this study, few statistical test were performed such as Descriptive Statistics, Independent T-Test, Analysis of Variance (ANOVA), Pearson's Correlation Analysis and Multiple Linear Regression. The study found that 81 % from the total respondent were ever absent from the class. The results also show that there were no difference in the students' perception towards absenteeism among gender and course. The finding also indicated the positive linear relationship between all of independent variables (Student Problem, Peer Influence, Teaching Style and Class Environment) with dependent variable (Students' Perception towards Absenteeism). Based on the regression analysis, it was found out that factors of student problem, peer influence and class environment were significantly influence the students' perception towards absenteeism. It is hoped that the outcome of this study will give benefits to all students and universities. In order to reduce the percentage of students' absenteeism, it is recommended to the lecturers to encourage students to come to the class.